Bhutan : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1994)
This paper describes economic developments in Bhutan during the 1990s. The paper discusses the fiscal outcome in 1993/94 (July-June) and the main elements of the authorities' budget proposals for 1994/95. It assesses monetary and credit developments, as well as the major initiatives adopted by the authorities in the area of financial sector reform. The paper analyzes balance-of-payments developments in 1993/94 and changes in the exchange and trade system. The paper also highlights that output was estimated to have risen by more than 5 percent in 1993.